Analisis Perlakuan Akuntansi Aset Tetap Berdasarkan SAK-ETAP Pada Puskopdit Swadaya Utama - Anastasia Relyani Laru; Wilhelmina Mitan; Konstantinus Pati Sanga (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
The aim of this research is to determine and analyze the accounting treatment of fixed assets based on SAK-ETAP at Puskopdit Swadaya Utama 2020-2021. The research method used is descriptive qualitative. The data sources used in this research are primary data and secondary data. Data collection techniques in this research used observation, interviews and documentation methods. The data analysis technique used is qualitative analysis, namely data collection and analysis, data reduction, data presentation, and verification or drawing conclusions. The results of this research show that the classification of fixed assets, acquisition and recognition of fixed assets, measurement of fixed assets, depreciation of fixed assets, and presentation of fixed assets in the balance sheet are in accordance with SAK-ETAP. Meanwhile, the termination and disposal of fixed assets is not in accordance with SAK-ETAP.